ZnO Production from EAF Solid Waste Using Hydrothermal Methods via Oxalate Precipitation - Prasetyo, Imam; Rozana, Monna; Astuti, Widi; Nulhakim, Lukman (Graduate School of Universitas Syiah Kuala, 2023)
Electric Arc Furnace (EAF) waste contains 50-60% Zn. EAF waste synthesis has the potential to produce ZnO, which can be used in a variety of applications. The hydrothermal method is used in the synthesis, with time variations of 3 and 6 hours and temperature variations of 120 C, 150 C and 200 C using precipitating reagents in the form of sodium hydroxide (NaOH) and oxalic acid (C2H2O4). UV-Vis spectrophotometer characterization result shows the absorbance value at 365 nm, which is the absorbance characteristic of ZnO material. The result of increasing the Zn element was revealed by XRF characterization. The XRD characterization revealed zinc oxalate dehydrates. This result depicts the hydrothermal with the oxalic acid solvent used to produce zinc oxalate dehydration at various temperatures and time variations.